Diving into hot topics of salivary gland carcinoma management—an EORTC young and early career investigator survey - Lorini, Luigi; Ronchi, Sara; Nevens, Daan; Klinghammer, Konrad; Orlandi, Ester; Bossi, Paolo; Szturz, Petr (Frontiers in Oncology, 2024)
IntroductionRecently, the ASCO and ESMO guidelines on salivary gland carcinomas (SGCs) have been released. However, several crucial points lack strong recommendations due to low or intermediate quality of evidence. To better address these “grey zones” in the guidelines, we conducted a survey among the European Organization for Research and Treatment of Cancer (EORTC) Head and Neck Cancer Group (HNCG) members on behalf of the EORTC young and early career investigators.Materials and methodsThe survey included 29 questions addressing diagnostic and therapeutic issues related to SGC patients and was shared among 539 members of the EORTC HNCG. Responses were collected from December 2022 to March 2023. The primary aim was to evaluate the decision-making criteria guiding physicians in areas with low evidence in SGC guidelines.ResultsWith a response rate of 19%, the survey received input from 102 respondents, mainly medical oncologists (45%). Among those with pathological high-risk features, 35% and 30% of respondents opted for chemoradiotherapy (CRT) in the definitive and adjuvant settings, respectively. For patients with R0 resection of highly aggressive SGC at the pT1–2 stage, 37% proposed a close follow-up, while 38% proposed adjuvant lymph-node field RT. In cases of pT3–4 stage, 48% proposed adjuvant lymph-node field RT in all cases, and 44% proposed it based only on risk factors. The most important factors guiding the decision to give adjuvant RT after salvage surgery for locoregional relapse include previous radiotherapy, margin status, and the presence of extranodal extension. When faced with combined positivity to HER2 and AR, responses regarding the choice of first-line palliative treatment were heterogeneous.ConclusionsInternational guidelines lack strong recommendations in several fields of SGC diagnosis and treatment due to insufficient high-quality data, resulting in heterogeneity in physicians’ treatment decision (e.g., adjuvant lymph-node field RT and their low concordance with guidelines, such as the use of concomitant CRT). The survey demonstrated the need for prospective clinical trial data to address these gaps in the future.